Modeling the Impact of Student Centered Learning Management and Analytical thinking of Primary School Students in Bangkok Metropolitan Region - Chantharattana, Weerawat (Journal of Multidisciplinary in Humanities and Social Sciences, 2020)
The purposes of this study were 1) to study the level of analytical thinking ability of primary school students in Bangkok Metropolitan region; 2) to group students based on the level of analytical thinking abilities; 3) to analyze a latent group of analytical thinking abilities of primary school students in Bangkok Metropolitan Region; and 4) to study the model of the causal relationship between Student-Centered Learning Management factors, student level factors and school level factors on analytical thinking abilities of primary school students in Bangkok Metropolitan Region. The sample was used 1,600 multi-stage random sampling. The survey instruments were 3 questionnaires and tests. The research results were found as follows; 1) The level of analytical thinking ability of primary school students in Bangkok Metropolitan Region had a good average score ( = 15.11, 75.55%); 2) The results of the analysis of latent groups based on the level of analytical abilities found that students can be classified into 3 groups; 3) Classification of latent groups of analytical thinking founds that the relationships between latent groups of analytical thinking ability had a relationship with the province; and 4) The model of the causal relationship between students centered learning management factors, targeting strategy factor, thinking strategy factor, the understanding that influence student’s analytical ability in student level and school level found that the model which the researcher created was consistent with the empirical data. Knowledge/Finding from this research currently. Student centered learners, cognitive strategy, and goal setting which indirectly influenced from student-centered learning management through cognitive strategy variables, cognition and goal setting variables with statistically significant.